Comparative Efficacy of Different Techniques of Oocyte Recovery from Slaughtered Goat Ovaries - Ashedkar, Poornima; R G, Bijurkar; Doddagoudar, Venkanagouda; Gond, Malasri (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to compare the efficacy of the oocyte quality and recovery rate between three different retrieval methods from goat ovaries. Recovery of oocytes by three methods that is slicing, aspiration and dissection followed by grading into Grade I, Grade II and Grade III oocytes was carried out. On statistical analysis, the mean oocyte recovery rate per ovary and mean yield of Grade I and II oocyte was significantly (p<0.05) higher in slicing as compared to aspiration, and no significant difference (p>0.05) was seen with dissection method. However, there was no significant difference between aspiration and dissection methods. There was no significant difference in the mean yield of Grade III oocytes between slicing, aspiration and dissection methods. In conclusion, slicing was found to be the more effective method for oocyte recovery.